2008
DOI: 10.1007/s10827-008-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased bradykinesia in Parkinson’s disease with increased movement complexity: elbow flexion–extension movements

Abstract: The present research investigates factors contributing to bradykinesia in the control of simple and complex voluntary limb movement in Parkinson's disease (PD) patients. The functional scheme of the basal ganglia (BG)-thalamocortical circuit was described by a mathematical model based on the mean firing rates of BG nuclei. PD was simulated as a reduction in dopamine levels, and a loss of functional segregation between two competing motor modules. In order to compare model simulations with performed movements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
1
17
1
Order By: Relevance
“…This leads to the speculation that the categorical action sequences used in the current study may have different preparation loads. And the different preparations may be due to movement complexity of sequences [39], [40]. However, in this study, the overall error rates among the three categories did not show statistical difference, and the movement onset latency among the three categories did not differ significantly either.…”
Section: Discussioncontrasting
confidence: 67%
“…This leads to the speculation that the categorical action sequences used in the current study may have different preparation loads. And the different preparations may be due to movement complexity of sequences [39], [40]. However, in this study, the overall error rates among the three categories did not show statistical difference, and the movement onset latency among the three categories did not differ significantly either.…”
Section: Discussioncontrasting
confidence: 67%
“…These four features were derived from data obtained during the writing tasks, which were more complex than the tracing tasks. Moroney et al [24] also showed in a simulation model that PD patients were slower than HC in both simple and complex movements, but slowness increased with increased movement complexity.…”
Section: Discussionmentioning
confidence: 95%
“…Inadequate force of the initial impulsive activity in the agonist (Hallett and Khoshbin, 1980), and inappropriate scaling of the dynamic muscle force to the movement parameters (Berardelli et al, 1986) are some likely reasons. It has been suggested that the impaired basal ganglia-thalamo-cortical pathway results in decreased basal ganglia outputs, which in turn produces slowed movements (Contreras-Vidal and Stelmach, 1995; Moroney et al, 2008). An alternative explanation is that the slowness of movement in PD is due to inadequately activated motor cortical and spinal cord centers because of dopamine reduction not only in basal ganglia, but also in cortical and spinal sites (Cutsuridis, 2011).…”
Section: Slowness Of Simple Repetitive Movementsmentioning
confidence: 99%